Exploring The Factors Affecting The Employees’ Productivity: A Case Study Of Selected SMEs In Lahore - Arshad, Summera; Fatima, Syeda Zain (Archives of Business Research, 2021)
Every company strives to improve the productivity of the employees so that it can increase its revenues. Several studies have conducted to find the factors that can influence the productivity of the employees. This study explored the factors that that can affect the productivity of the employees in selected SMEs of Lahore. Focus group interviews were conducted to gather the data and open-ended questions were asked of employees. Study finds that productivity is affected by cooperation between colleagues, discrimination, and harassment. Moreover, it is also affected by work-life imbalance. It has also been explored that productivity is affected by financial rewards and unbiased evaluations. It is important for the companies to focus on these issues so that productivity of the employees can be improved.